Histopatogenicidade de Blastocystis SP para camundongos Swiss - Pavanelli, Mariana Felgueira (2012)
Blastocystis sp is an enteric protozoan with few studies about its pathogenic potential in experimental models. In this work the Blastocystis sp pathogenicity in gastrointestinal tract of mice was evaluated according to the inoculum and duration of infection. Male Swiss mice were infected intragastrically, with 100, 500, 1,000, 5,000 and 10,000 Blastocystis sp cystic forms which were obtained from a mixture of eight isolated human who were cultured in Jones medium. After 7, 14, 21, 28 and 60 days of infection, the animals were sacrificed and fragments of the small, large and cecum intestine were taken for histopathological analysis. Concomitantly to animals infection, the cystic forms of the isolated human were washed and purified for DNA extraction. The gene of ribosomal RNA (SSU-rRNA) was amplified and the products were digested with AluI restriction enzyme to analyze the restriction fragment length polymorphism (RFLP). Blastocystis sp triggered inflammatory response in different tissues that were analyzed, predominantly mononuclear infiltrate. A predilection by the cecum intestine with invasive character was observed by finding cysts in the muscular layer. Greater inocula triggered earlier inflammatory processes (7 days) and smaller inocula, later (from 21 days). Molecular analysis identified subtypes 1 and 3 that could not be related to pathogenicity, because the inocula were obtained from a mixture of isolated. We concludethat in the proposed model the pathogenicity of Blastocystis sp isolates studied, is related tothe inoculum and duration of infection.